Preparation method of anisotropic ceramic aerogel based on ceramic particles

Through the 3D printing or mold molding technology that is frozen in situ in situ, all directional ceramic gels with a high -oriented heterosexual ratio and excellent mechanical properties are prepared, which solves the existing products in terms of cost, manufacturing complexity and mechanical performance. Insufficient, realize the important practical significance of the industrialization of ceramic gas gel.

CN119330740APending Publication Date: 2025-01-21SOUTHEAST UNIV

Patent Information

Application Number
CN202411467854.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing anisotropic ceramic aerogels have shortcomings in terms of mechanical properties, cost and manufacturing complexity, especially the high price of products based on fiber materials, complex preparation methods and lack stiffness.

Method used

In-situ freezing-assisted 3D printing or mold forming technology is used to prepare anisotropic ceramics with directional pore structures by mixing ceramic particles, binders and solvents, stirring and shaping, followed by freeze drying and gradient temperature sintering. Aerogel.

Benefits of technology

It achieves a high anisotropy ratio of ceramic aerogels, with high stiffness and compressibility in two orthogonal directions, while maintaining good thermal insulation, noise reduction and mechanical properties. The process is simple, low cost and suitable for batch production. chemical production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330740A_ABST
    Figure CN119330740A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of anisotropic ceramic aerogel based on ceramic particles. The preparation method comprises the following steps: firstly, adding ceramic particles and a binder into a water solvent according to a ratio, and uniformly stirring to prepare ceramic aerogel slurry; and secondly, filling the slurry into a mold or an extrusion needle tube of a direct-writing 3D printing technology, and preparing or printing anisotropic structure aerogel in any shape on a cooled copper plate according to a pre-designed structure by adopting an in-situ freezing technology as an assistance. After freeze drying and sintering, the ceramic aerogel with the directional hole structure on the microscopic scale is finally obtained. The anisotropic ceramic aerogel has excellent mechanical properties, has an ultrahigh anisotropic coefficient up to 24, and has high rigidity and high compressibility in two orthogonal directions respectively. The ceramic aerogel also has the functions of heat insulation, noise reduction, adsorption, vibration reduction and the like. The method for preparing the anisotropic ceramic aerogel through the in-situ freezing auxiliary mold forming or 3D printing technology is low in cost, easy to operate and wide in application range and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic aerogels using ceramic particles as raw materials, and in particular to a method for preparing anisotropic ceramic aerogels based on ceramic particles. Background Art

[0002] Ceramic aerogel is a highly porous structural material that is widely used in thermal insulation, shock absorption and other fields. The demand for high-performance ceramic aerogel is growing. At present, a major challenge in the development of ceramic aerogel is to design, quickly and cheaply manufacture ceramic aerogels with excellent mechanical properties.

[0003] Anisotropic ceramic aerogels are aerogels with highly arranged directional pores, which can exhibit different properties such as thermal insulation, microwave absorption, and mechanical properties in different directions. Most of the existing anisotropic ceramic aerogels are based on fiber materials, which are not only expensive and complicated to prepare, but also lack rigidity in fiber-based ceramic aerogels, making it difficult to meet actual needs. Anisotropic ceramic aerogels based on ceramic particles can not only meet the needs of fast and low-cost manufacturing, but also solve the problem that traditional particle-based ceramic aerogels lack anisotropy and are often brittle. Particle-based anisotropic ceramic aerogels have high rigidity and compressibility in different directions, which is of great practical significance for promoting the industrialization of ceramic aerogels.

[0004] In order to further improve the anisotropy and mechanical properties of particle-based ceramic aerogels, the design of highly arranged microscopic directional pore structures has great potential in enhancing the mechanical properties of ceramic aerogels. Microstructure design can make ceramic aerogels have stiffness and compressibility in different directions. However, anisotropic ceramic aerogels also bring great challenges to manufacturing. In-situ freezing-assisted 3D printing or mold forming technology can meet the efficient production and personalized design of ceramic aerogels, but the preparation of complex microstructures requires higher control precision and higher requirements for raw materials, which increases the cost and difficulty of manufacturing. Summary of the invention

[0005] The purpose of the present invention is to address the problems existing in the background technology and propose a method for preparing anisotropic ceramic aerogel based on ceramic particles, using in-situ freezing-assisted 3D printing or mold forming technology to prepare the anisotropic ceramic aerogel; the mold forming and 3D printing method for preparing ceramic aerogel proposed in the present invention is novel, simple in process, and low in cost, and can realize the arbitrary multi-scale geometric structure and microstructure of the aerogel, which has important application value for the development of high-performance anisotropic ceramic aerogel.

[0006] The technical solution of the present invention is a method for preparing anisotropic ceramic aerogel based on ceramic particles, comprising the following specific steps:

[0007] S1. Prepare raw materials; mix ceramic particles, adhesive and solvent in a certain mass ratio and stir them;

[0008] S2, molding processing: processing the processed raw materials into semi-finished products through additive manufacturing or mold molding;

[0009] S3, freeze-drying the semi-finished product obtained in step S2;

[0010] S4, placing the product in step S3 into a muffle furnace, increasing the temperature in a gradient manner, and sintering at a high temperature for a period of time to obtain an anisotropic ceramic aerogel having a directional pore structure on a microscopic scale.

[0011] Preferably, the ceramic particle material in step S1 is selected from one or more combinations of aluminum oxide, silicon dioxide, zirconium oxide, titanium oxide, zinc oxide, yttrium oxide, silicon carbide, mullite, boron nitride, silicon nitride, aluminum nitride, calcium silicate, aluminum silicate, magnesium titanate, barium titanate, and hydroxyapatite.

[0012] Preferably, in step S1, the binder is selected from one or more combinations of cellulose nanofibers, sodium alginate, chitosan, polyvinyl alcohol, carrageenan, guar gum, xanthan gum, gum arabic, pectin, gelatin, lignin, and epoxy resin; and the solvent is water.

[0013] Preferably, in step S1, the mass ratio of ceramic particles to binder is 4-10:1-3, and the ratio of solvent added is 1-10 ml / g; during stirring in step S1, a stirrer is used to stir for 1-2 hours to fully mix.

[0014] Preferably, when the additive manufacturing method is used in step S2:

[0015] The raw materials in step S1 are loaded into an ink direct writing 3D printer as printing ink, and an in-situ freezing technology is used as an auxiliary to design and print an anisotropic ceramic aerogel semi-finished product on a cooled substrate;

[0016] Among them, the nozzle diameter of the ink direct writing 3D printer in S2 is 50-1600um, the printing pressure is 10-120psi, and the needle speed is 1-50mm / s;

[0017] The shapes of anisotropic ceramic aerogels printed by the ink direct writing 3D printer in the S2 can be customized, including grids, snakes, aerogel covers or snowflakes.

[0018] Preferably, when the mold forming method is adopted in step S2:

[0019] The raw materials in step S1 are poured into a mold as slurry, and a large-scale anisotropic ceramic aerogel semi-finished product is prepared by directional freezing technology;

[0020] The shape of the mold in step S2 is any shape, such as rectangle, trapezoid, triangle, star, etc., and the size scale is 0.01-50m.

[0021] Preferably, the temperature of the substrate in S2 ranges from -150°C to -10°C, and the substrate material is copper, iron, stainless steel, alloy or a combination thereof.

[0022] Preferably, the freeze-drying time in step S3 is 1 to 24 hours, and the freeze-drying temperature is -10 to -50°C.

[0023] Preferably, the temperature gradually increased in step S4 is 200-2000° C., and the high-temperature sintering time is 1-36 h.

[0024] An anisotropic ceramic aerogel based on ceramic particles is prepared using the above method. The prepared anisotropic ceramic aerogel has an anisotropy ratio (ratio of axial modulus to radial modulus) of up to 24 in the axial direction, high stiffness in the axial direction and compressibility in the radial direction.

[0025] Preferably, ceramic aerogel has good thermal insulation, noise reduction and mechanical protection properties.

[0026] Compared with the prior art, the present invention has the following beneficial technical effects: 1. Excellent anisotropy and mechanical properties: Compared with traditional ceramic aerogels, the method for preparing anisotropic ceramic aerogels by mold forming or 3D printing technology proposed in the present invention can achieve an ultra-high anisotropy ratio, high stiffness and compressibility in two orthogonal directions, while maintaining good thermal insulation, noise reduction and mechanical properties.

[0027] 2. Simplified process and low cost: The present invention provides a mold forming or 3D printing method assisted by directional freezing technology, which has a simple process and low cost and is suitable for mass production.

[0028] 3. Optimized microstructure: Through directional freezing technology, the preparation of ceramic aerogel microporous structure is realized, which improves the thermal insulation, noise reduction and mechanical properties of ceramic aerogel.

[0029] 4. Adjustable macroscopic geometric structure: The ceramic aerogel prepared by the method of the present invention has an adjustable macroscopic structure, which further promotes the practical application of ceramic aerogel through personalized design.

[0030] 5. Adjustable microporous structure: By adjusting the ratio of raw materials, the temperature of directional freezing and the drying time, the ceramic aerogel prepared by the method of the present invention has an adjustable microporous structure, which can change the number and size of the microporous structure distribution.

[0031] 6. Wide applicability: The method for preparing anisotropic ceramic aerogels proposed in the present invention is also applicable to the preparation of ceramic aerogels in ceramic fiber systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Microscopic SEM images of 3D printed particle-based anisotropic silica aerogel before and after sintering;

[0033] Figure 2 A diagram showing the personalized structure of 3D-printed silica ceramic aerogel;

[0034] Figure 3 for the processability of anisotropic and isotropic silica aerogels;

[0035] Figure 4 The compression performance test diagrams of anisotropic and isotropic silica aerogels in different directions;

[0036] Figure 5 is the thermal conductivity of anisotropic silica aerogel in different directions;

[0037] Figure 6 Comparison of the noise reduction performance of anisotropic and isotropic silica aerogels;

[0038] Figure 7 This is a cross-sectional microscopic SEM image of anisotropic silicon carbide-alumina aerogel;

[0039] Figure 8 This is a cross-sectional SEM image of anisotropic silicon carbide-boron nitride aerogel. DETAILED DESCRIPTION

[0040] Example 1

[0041] An anisotropic ceramic aerogel prepared by in-situ freezing-assisted 3D printing or mold forming technology based on ceramic particles, the preparation method thereof comprises the following steps:

[0042] 1. Mix silica particles, sodium alginate and water in a mass ratio of 7:4:2, stir for 1 hour until the mixture is uniform, and prepare mold slurry and printing ink.

[0043] 2. Pour the slurry into the mold and freeze it on a copper plate at -80°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 200 microns, a printing pressure of 20 psi, and a needle speed of 10 mm / s, and perform in-situ cryo-printing on a copper plate at -80°C.

[0044] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 10 h at a temperature of -40°C.

[0045] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1000°C, and sinter for 1 hour.

[0046] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0047] Example 2

[0048] An anisotropic ceramic aerogel based on ceramic particles prepared by in-situ freezing-assisted 3D printing or mold forming technology, the preparation method of which comprises the following steps:

[0049] 1. Mix alumina particles, cellulose and water in a mass ratio of 7:3:2, stir for 2 hours until the mixture is uniform, and prepare mold slurry and printing ink.

[0050] 2. Pour the slurry into the mold and freeze it on a copper plate at -70°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 400 microns, a printing pressure of 30 psi, and a needle speed of 15 mm / s, and perform in-situ freeze printing on a copper plate at -70°C.

[0051] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 8 h at a temperature of -30°C.

[0052] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1200°C, and sinter for 2 hours.

[0053] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0054] Example 3

[0055] An anisotropic ceramic aerogel based on ceramic particles prepared by in-situ freezing-assisted 3D printing or mold forming technology, the preparation method of which comprises the following steps:

[0056] 1. Mix mullite particles, chitosan and water in a mass ratio of 6:5:3, stir for 3 hours until the mixture is uniform, and prepare mold slurry and printing ink.

[0057] 2. Pour the slurry into the mold and freeze it on a copper plate at -60°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 400 microns, a printing pressure of 35 psi, and a needle speed of 20 mm / s, and perform in-situ freeze printing on a copper plate at -60°C.

[0058] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 9 h at a temperature of -40°C.

[0059] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1500°C, and sinter for 3 hours.

[0060] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0061] Example 4

[0062] An anisotropic ceramic aerogel based on ceramic particles prepared by in-situ freezing-assisted 3D printing or mold forming technology, the preparation method of which comprises the following steps:

[0063] 1. Mix silicon carbide particles, xanthan gum and water in a mass ratio of 6:1:2, stir for 2.5 hours until the mixture is uniform, and prepare mold slurry and printing ink.

[0064] 2. Pour the slurry into the mold and freeze it on a copper plate at -75°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 350 microns, a printing pressure of 30 psi, and a needle speed of 25 mm / s, and perform in-situ freeze printing on a copper plate at -75°C.

[0065] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 10 h at a temperature of -45 °C.

[0066] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1100°C, and sinter for 2 hours.

[0067] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0068] Example 5

[0069] An anisotropic ceramic aerogel based on ceramic particles prepared by in-situ freezing-assisted 3D printing or mold forming technology, the preparation method of which comprises the following steps:

[0070] 1. Mix silicon carbide particles, alumina particles, silicon dioxide particles, sodium alginate and water in a mass ratio of 6:2:1:1:2, stir for 3 hours until the mixture is uniform, and prepare mold slurry and printing ink.

[0071] 2. Pour the slurry into the mold and freeze it on a copper plate at -90°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 400 microns, a printing pressure of 20psi, and a needle speed of 20mm / s, and perform in-situ freeze printing on a copper plate at -90°C.

[0072] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 12 h at a temperature of -50 °C.

[0073] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1500°C, and sinter for 3 hours.

[0074] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0075] Example 6

[0076] An anisotropic ceramic aerogel based on ceramic particles prepared by in-situ freezing-assisted 3D printing or mold forming technology, the preparation method of which comprises the following steps:

[0077] 1. Mix hydroxyapatite particles, zinc oxide particles, sodium alginate and water in a mass ratio of 4:3:3:3, stir for 2 hours until the mixture is uniform, and prepare mold slurry and printing ink.

[0078] 2. Pour the slurry into the mold and freeze it on a copper plate at -75°C; or load the printing ink into a direct writing 3D printer with a nozzle diameter of 350 microns, a printing pressure of 20 psi, and a needle speed of 25 mm / s, and perform in-situ freeze printing on a copper plate at -75°C.

[0079] 3. The anisotropic ceramic aerogel obtained by mold forming or printing was freeze-dried for 11 h at a temperature of -40 °C.

[0080] 4. Place the anisotropic ceramic aerogel in a muffle furnace, increase the temperature gradually to 1350°C, and sinter for 2 hours.

[0081] 5. Obtain anisotropic ceramic aerogels with a highly aligned directional pore structure at the microscopic level.

[0082] Comparative Example 1

[0083] The performance of the ceramic aerogels prepared in Examples 1-6 was tested.

[0084] Anisotropy test steps:

[0085] First, the ceramic aerogel prepared in Examples 1-6 is placed on the platform of a universal testing machine, and the ceramic aerogel is compressed axially and radially respectively; then, the slope of the ceramic aerogel in the elastic strain state is taken as the compression modulus; the test is recorded three times respectively and the average value is taken; the ratio of the compression moduli in the two directions is taken to obtain the anisotropy ratio; and finite element software is further used to carry out finite element analysis (FEA) to study the strain behavior of the ceramic aerogel in the compression state.

[0086] Thermal conductivity test steps:

[0087] A 2 mm thick ceramic aerogel was placed on a thermal conductivity platform to measure the thermal conductivity and error. The method used was the ASTM-5470 reference rod method, and the thermal conductivity and error were calculated by fitting.

[0088] Noise reduction coefficient test steps:

[0089] The ceramic aerogel was placed at the right end of the test tube, and the horn was controlled by RIGOL (DG1032) to introduce 200-2500Hz noise sound waves from the left end of the 30mm pipe. The returned data was then analyzed by VK701. The sound absorption coefficient was converted and smoothed using MATLAB. The arithmetic mean of the sound absorption coefficients at 250Hz, 500Hz, 1000Hz, and 2000Hz was taken to obtain the noise reduction coefficient.

[0090] The test results are shown in the following table:

[0091] Table 1 Example parameters and ceramic aerogel properties

[0092]

[0093]

[0094] Analysis of the experimental data in Table 1 shows that mechanical, thermal and acoustic tests on ceramic aerogels can achieve ultra-high anisotropy ratios, high hardness in the axial direction and high compressibility in the radial direction; and excellent thermal insulation and noise reduction capabilities. This shows that the particle-based anisotropic ceramic aerogels prepared by this method can achieve ultra-high anisotropy ratios in mechanical properties while maintaining good thermal insulation and noise reduction capabilities.

[0095] like Figure 3 As shown, the particle-based anisotropic ceramic aerogel prepared by the method of the present invention has processability in the axial direction, which is conducive to industrial production.

[0096] like Figure 4 , Figure 5 and Figure 6As shown in Figure 2, anisotropic ceramic aerogels have superior mechanical properties, thermal insulation and noise reduction properties compared to isotropic ceramic aerogels. These excellent properties highlight the advantages of ceramic aerogels with highly oriented micropores, which are beneficial for noise absorption and thermal insulation, and have high hardness and high compressibility in orthogonal directions.

[0097] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for preparing anisotropic ceramic aerogel based on ceramic particles, characterized in that: The specific steps include: S1. Prepare raw materials; mix ceramic particles, adhesive and solvent in a certain mass ratio and stir them; S2, molding processing: processing the processed raw materials into semi-finished products through additive manufacturing or mold molding; S3, freeze-drying the semi-finished product obtained in step S2; S4, placing the product in step S3 into a muffle furnace, increasing the temperature in a gradient manner, and sintering at a high temperature for a period of time to obtain an anisotropic ceramic aerogel having a directional pore structure on a microscopic scale.

2. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: In step S1, the ceramic particle material is selected from one or more combinations of aluminum oxide, silicon dioxide, zirconium oxide, titanium oxide, zinc oxide, yttrium oxide, silicon carbide, mullite, boron nitride, silicon nitride, aluminum nitride, calcium silicate, aluminum silicate, magnesium titanate, barium titanate, and hydroxyapatite.

3. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: In step S1, the adhesive is selected from one or more combinations of cellulose nanofibers, sodium alginate, chitosan, polyvinyl alcohol, carrageenan, guar gum, xanthan gum, gum arabic, pectin, gelatin, lignin, and epoxy resin; and the solvent is water.

4. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: In step S1, the mass ratio of ceramic particles to binder is 4-10:1-3, and the ratio of solvent added is 1-10 ml / g; during stirring in step S1, a stirrer is used to stir for 1-2 hours to fully mix.

5. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: When the additive manufacturing method is used in step S2: The raw materials in step S1 are loaded into an ink direct writing 3D printer as printing ink, and an in-situ freezing technology is used as an auxiliary to design and print an anisotropic ceramic aerogel semi-finished product on a cooled substrate; Among them, the nozzle diameter of the ink direct writing 3D printer in S2 is 50-1600um, the printing pressure is 10-120psi, and the needle speed is 1-50mm / s; The shapes of anisotropic ceramic aerogels printed by the ink direct writing 3D printer in the S2 can be customized, including grids, snakes, aerogel covers or snowflakes.

6. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: When the mold forming method is used in step S2: The raw materials in step S1 are poured into a mold as slurry, and a large-scale anisotropic ceramic aerogel semi-finished product is prepared by directional freezing technology; Among them, the shape of the mold in step S2 is rectangular, trapezoidal, triangular, or star-shaped, and the size scale is 0.01-50m.

7. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 5, characterized in that: The temperature of the substrate in S2 ranges from -150°C to -10°C, and the substrate material is copper, iron, stainless steel or a combination thereof.

8. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 5 or 6, characterized in that: The freeze drying time in step S3 is 1 to 24 hours, and the freeze drying temperature is -10 to -50°C.

9. The method for preparing anisotropic ceramic aerogel based on ceramic particles according to claim 1, characterized in that: In step S4, the temperature gradually increased to is 200-2000° C., and the high-temperature sintering time is 1-36 hours.

10. An anisotropic ceramic aerogel based on ceramic particles, prepared by the method according to any one of claims 1 to 9, characterized in that: The prepared anisotropic ceramic aerogel is a ceramic aerogel with high rigidity in the axial direction and compressibility in the radial direction.

Citation Information

Patent Citations

  • Method for preparing porous ceramic with directional pore structure

    CN101423378A

  • Method for preparing material with controllable macro and micro structures

    CN109400179A

Cited By

  • A bionic double-network nanofiber aerogel with integrated high-temperature thermal insulation, low-frequency noise reduction, and fire retardant functions and its preparation method

    CN120040167B

  • Coaxial 3D printing hollow aerogel fiber as well as preparation method and application thereof

    CN121629566A